Academic vs. Private Practice: An Indistinct Distinction - Andrews, R. Torrance (Seminars in Interventional Radiology, 2019)
Interventional radiology (IR) practices take many forms, but often are distinguished as following either an academic or private practice model. Both differences and similarities are seen when comparing these two general practice categories, and often the line between the two models is unclear. This article reviews some of the commonalities and differences between academic and private practice IR, and provides personal insights from an author who has significant experience in both practice models.
Keywords: interventional radiology; private practice; academic; education; clinical practice